2006
DOI: 10.1111/j.1365-2672.2006.02956.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli O157:H7 in wastewater from dairy lagoons

Abstract: Aim:  To determine the survival of Escherichia coli O157:H7 in dairy wastewater from on‐site holding lagoons equipped with or without circulating aerators. Methods and Results:  Survival was monitored in dairy lagoon microcosms equipped with or without scale‐size circulators. Both laboratory strains of E. coli O157:H7 and an isolate of E. coli H7 from wastewater had poor survival rates and none proliferated in water from waste lagoons with or without circulators. Furthermore, the decline of E. coli O157:H7 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
50
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 44 publications
4
50
1
Order By: Relevance
“…The pathogen is known to be shed in manure by cattle and survives in animal waste and wastewater (2,11,14,22,25). Owing to its low prevalence (13,14,25), the pathogen could not be detected in manure and wastewater from dairies in the central valley of California (27,31). It is likely that the pathogen could escape detection at low cell numbers or as nonculturable cells (32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogen is known to be shed in manure by cattle and survives in animal waste and wastewater (2,11,14,22,25). Owing to its low prevalence (13,14,25), the pathogen could not be detected in manure and wastewater from dairies in the central valley of California (27,31). It is likely that the pathogen could escape detection at low cell numbers or as nonculturable cells (32).…”
mentioning
confidence: 99%
“…Although E. coli O157:H7 can be isolated even after 21 months (24) by selective enrichments from a manure pile from inoculated sheep, the pathogen failed to grow and decline rapidly in manure, manure slurries, and wastewater from dairy lagoons (2,17,31). In addition, feeding cattle with a straw-rich diet (12), silage made with bacteriocin-producing bacteria (3), and competitive exclusion products using lactic acid bacteria (7), colicinogenic E. coli (8,33) and O157-specific bacteriophages (35) has the potential to inhibit pathogen replication inside the animals.…”
mentioning
confidence: 99%
“…paratuberculosis, Salmonella spp., Yersinia spp., Giardia lamblia, and Cryptosporidium parvum (38,39,40). While numerous studies have measured the occurrence of these zoonotic pathogens in cattle manures and assessed their fate and transport in the environment (41,48,55), to our knowledge, no comprehensive studies have been conducted to quantify pathogens in dairy wastewaters. In addition, only a few studies to date have quantified a wide range of pathogens within cattle manures (20,21,26).…”
mentioning
confidence: 99%
“…While the greatest number of detections for all organisms occurred in that first month of analysis, the number of positive pond results generally decreased during each subsequent month. The decrease in the number of detections may have been affected by the pathogen-shedding rate of the cattle, environmental variables (e.g., solar irradiation, temperature), pond characteristics (e.g., solids content), or competition from other indigenous microorganisms leading to a reduction of pathogen survival in the ponds (29,41,42). The fact that Leptospira spp.…”
mentioning
confidence: 99%
“…EHEC can be transmitted from contaminated cattle manure and irrigation water to agricultural products, such as lettuce [11] [12]. Ravva et al [10] showed that E. coli O157:H7 failed to proliferate in dairy lagoon wastewater microcosms, indicating that EHEC could be removed from wastewater system. Some ciliate protozoa were found to be resistant to E. coli O157:H7 and also able to reduce E. coli populations in dairy lagoon wastewater [13].…”
Section: Introductionmentioning
confidence: 99%